Auditor Industry Specialization, Institutional Ownership, and Independent Commissioners on Integrity of Financial Report: The Moderating Role of Audit Quality - Indra Yusuf; Muhyarsyah (Owner : Riset dan Jurnal Akuntansi, 2026)
This study investigates the effect of auditor industry specialization, institutional ownership, and independent commissioners on financial reporting integrity, with audit quality as a moderating variable. The research focuses on consumer goods manufacturing companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The study is motivated by concerns regarding the reliability of financial reporting amid recurring cases of financial statement manipulation that undermine investor and public trust. A quantitative approach is employed using panel data regression and Moderated Regression Analysis (MRA). From a population of 132 firms, 35 companies met the sampling criteria, resulting in 175 firm-year observations. The Fixed Effects Model (FEM) was selected as the most appropriate panel regression model. Financial reporting integrity is treated as the dependent variable, while auditor industry specialization, institutional ownership, and independent commissioners serve as independent variables, with audit quality acting as the moderating variable. The results show that auditor industry specialization and institutional ownership have a positive and significant effect on financial reporting integrity, whereas independent commissioners do not have a significant effect. Furthermore, audit quality moderates the relationship between auditor industry specialization and financial reporting integrity, strengthening its influence. However, audit quality does not moderate the relationship between institutional ownership or independent commissioners and financial reporting integrity. These findings indicate that external governance mechanisms supported by high audit quality are more effective in improving financial reporting integrity than internal governance mechanisms alone. This study contributes to the accounting and auditing literature and provides insights for regulators, auditors, and corporate management in enhancing the credibility of financial reporting.